2016
DOI: 10.3174/ajnr.a4867
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Weighted Imaging for Predicting and Monitoring Primary Central Nervous System Lymphoma Treatment Response

Abstract: BACKGROUND AND PURPOSE:Whether ADC value predicts the therapy response and outcomes of primary central system lymphoma remains controversial. This study assessed the minimum ADC correlated with treatment response in patients with primary central nervous system lymphoma undergoing methotrexate-based chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 21 publications
1
32
0
Order By: Relevance
“…A high ADC corresponds to increased water mobility towards free diffusion, and conversely a low ADC corresponds to restricted diffusion. In a densely cellular homogeneous tumour, such as lymphoma, treatment-related ADC changes may be as high as 50% 4 , however treatment responses may be heterogeneous due to regional micro environmental factors or genetic variation 5 – 7 . A recent animal model study of ovarian tumours showed an average 7.5% increase in mean ADC after treatment but identified significant spatial heterogeneity due to variations in tumour response 7 .…”
Section: Introductionmentioning
confidence: 99%
“…A high ADC corresponds to increased water mobility towards free diffusion, and conversely a low ADC corresponds to restricted diffusion. In a densely cellular homogeneous tumour, such as lymphoma, treatment-related ADC changes may be as high as 50% 4 , however treatment responses may be heterogeneous due to regional micro environmental factors or genetic variation 5 – 7 . A recent animal model study of ovarian tumours showed an average 7.5% increase in mean ADC after treatment but identified significant spatial heterogeneity due to variations in tumour response 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that the ADC min -post and the percentage change of ADC min could predict the local control. Another study conducted by our team demonstrated that pre-therapeutic ADC min failed to predict the primary central nervous system lymphoma outcomes, but ADC min changes and percentage changes after one cycle of chemotherapy could more precisely predict treatment responses 18 . A possible explanation is that pre-therapeutic intratumoral cell density and stromal space cannot precisely reflect the treatment response.…”
Section: Discussionmentioning
confidence: 97%
“…9 Specifically, apparent diffusion coefficient values derived from DWI have been shown to correlate with tumor cellularity, glioma grade, and treatment response. [9][10][11][12][13] Moreover, recent studies have shown that DWI parameters may differentiate the histology of BM from lung cancer. 14,15 However, the association between DWI parameters and the gene mutation status has not been assessed for BM from lung cancer, to our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Such patients are expected to respond well to noninvasive TKI treatment, and clinicians can plan this treatment accordingly if the mutation status is known. Moreover, Huang et al 13 recently reported that ADC min has the potential to predict and monitor the response of primary CNS lymphoma to chemotherapy. Therefore, through further study, we can apply serial ADC values to predict the response of BM from lung adenocarcinoma with EGFR mutations to TKI treatment.…”
Section: Discussionmentioning
confidence: 99%